Incidence and clinical-pathological correlation of ectopic pregnancy - "Archbishop Loayza Hospital" in 1985-1989. - Bautista Kiota, Margarita (2015)
In the Arzobispo Loayza Hospital during the period January 1985 December 1989 was study the clinic- pathology incidence and correlation of ectopic gestation. There was found an incidence of 1,50% of the total of attended deliveries; 1 ectopic gestation every 67 deliveries; This number is the highest ever found in natural and international literature. Also there was clinic- pathologic correlation in the 91% of the cases. Was found that it is  more frequently in the women that ever had delivered or that only had delivered one time, the predominant edge of the group was between 25 and 34 years. The most frequency location is the ectopic tubal gestation, it was the 97,8% of the cases; of that the 60,2% were at the right side. Complicated with hemoperitoneum was the 86.9% at the moment of the operation. The 67,4% was diagnosticated between the 5.th and 8.th week of amenorrea. There was found the probable causal factor in the 62% of the cases. The management was in charge of the Gin ecology Service. 5 cases were operated by the gynecology service. Other 5 cases were operated by the Surgery Service and corresponded to patients that came to the hospital by emergency; 4 of that were without gynecology evaluation.